Leading by Example? European Union Implementation of Cultural Diversity in Internal and External Audiovisual Policies - Pauwels, Caroline; Loisen, Jan (Javnost-The Public, 2016)
This article aims to assess how the European Union (EU) deals with cultural diversity in the audiovisual sector in both its policy discourse and practice. The underlying question guiding the analysis is whether the EU commits to implementing policies to enhance cultural diversity. A first part gives an overview of the concept’s development in time and in response to a specific political and economic context. The second part addresses implementation of the concept in the EU’s internal market project and its external trade relations by means of an analysis of four distinct policy areas: the evolution of the main underlying regulatory framework; European support programmes for the audiovisual sector; competition policies targeting the sector; and dealing with the audiovisual sector in external trade relations. On the basis of this analysis, we aim to evaluate in a final concluding part the coherence of the overall EU approach and the prospects and pitfalls for increased cultural diversity in the audiovisual sector in Europe. We argue that the strong focus of the EU on cultural diversity in its discourse has led to some steps of policy implementation which generates a fledgling positive, albeit fragile and imperfect, dynamic for cultural diversity.